2022
DOI: 10.3389/fcosc.2022.913668
|View full text |Cite
|
Sign up to set email alerts
|

Conservation through connection: Approaches to engaging communities in applied grizzly bear research

Abstract: Human-wildlife dynamics is a growing field and one of considerable importance to conservation. Wild spaces are in short supply, and consequently wildlife and people increasingly share the landscape, though not necessarily by choice. As a result, peoples’ needs might not be prioritized over those of wildlife, even in cases of human-wildlife conflict. For wildlife conservation to be effective and human-wildlife coexistence possible, the needs of both wildlife and people must be simultaneously addressed. Rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Another advantage of GrizzTracker was engaging the public in an active and meaningful way, which is an important factor in the success of community science and government-directed conservation programs (Newman et al 2012;Ceccaroni et al 2019). When asked why community scientists chose to participate in GrizzTracker, we found it was because our program provided an intriguing opportunity to contribute to grizzly bear science and land management decisions, similar to other research exploring community science (Bonney et al 2009;Wright et al 2015;Bloom and Crowder 2020;Hughes et al 2022aHughes et al , 2022b. We also found that community scientists were motivated to recruit their friends, family, or colleagues, further suggesting that GrizzTracker presented a unique and interesting engagement opportunity.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Another advantage of GrizzTracker was engaging the public in an active and meaningful way, which is an important factor in the success of community science and government-directed conservation programs (Newman et al 2012;Ceccaroni et al 2019). When asked why community scientists chose to participate in GrizzTracker, we found it was because our program provided an intriguing opportunity to contribute to grizzly bear science and land management decisions, similar to other research exploring community science (Bonney et al 2009;Wright et al 2015;Bloom and Crowder 2020;Hughes et al 2022aHughes et al , 2022b. We also found that community scientists were motivated to recruit their friends, family, or colleagues, further suggesting that GrizzTracker presented a unique and interesting engagement opportunity.…”
Section: Discussionmentioning
confidence: 73%
“…However, we do note a critical gap in our engagement efforts, including a lack of Indigenous community scientists as well as agricultural landowners, as noted in Hughes et al (2022a). We therefore suggest that others interested in pursuing community science projects would be well served to carefully consider the value of adopting multiple forms of engagement and educational strategies, seeking out formal and informal collaborations with various individuals and groups, and carefully consider and plan for an inclusive program to help achieve a project's intended outcomes (Hughes et al 2022a(Hughes et al , 2022b.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations